The Assistance For Composing House Management in Khajuma Community Self-Subsistent Agency Siantan Hilir Sub District: Pendampingan Pengelolaan Rumah Kompos di Badan Keswadayaan Masyarakat (BKM) Khajuma Kelurahan Siantan Hilir - Donna Youlla; Lathifah Khairani; Ellyta Ellyta (Yayasan Ahmar Cendekia Indonesia, 2022)
The Community Self-Subsistent Agency (BKM) is one of the village-level social institutions established by the government. The function of BKM is to help the poor in dealing with the problem of poverty through empowerment programs from the government, so that they are able to carry out activities to meet their daily needs. This Community Service (PKM) activity is in collaboration with BKM Khajuma which is located on Jalan Khatulistiwa, Siantan Hilir Village. The objectives of this activity are: 1) to utilize organic waste from plant residues that exist among community, 2) to conduct training on making Local Micro Organisms (MOL), 3) to manage existing compost houses so that they become better. The implementation of this service is focused on several activities which include organic waste management such as sorting organic and inorganic waste, demonstrations of making Local Micro Organisms (MOL) from fruit and vegetable waste, as well as assistance in managing the compost house that was just built in the BKM area. While the specific target to be achieved is that there will be an increase in the knowledge and skills of the community, especially with the compost house in their midst. Abstrak Badan Keswadyaan Masyarakat (BKM) merupakan salah satu lembaga kemasyarakatan tingkat Kelurahan yang dibentuk oleh pemerintah. Fungsi BKM yaitu untuk membantu masyarakat miskin dalam menghadapi masalah kemiskinan melalui program pemberdayaan dari pemerintah, agar mereka mampu melakukan aktifitas untuk memenuhi kebutuhan hidupnya. Kegiatan Pengabdian Kepada Masyarakat (PKM) ini bekerjasama dengan BKM Khajuma yang bertempat di Jalan Khatulistiwa, Kelurahan Siantan Hilir. Tujuan dari kegiatan ini adalah : : 1) untuk memanfaatkan sampah organik sisa tanaman yang ada di masyarakat, 2) untuk melakukan pelatihan pembuatan Mikro Organisme Lokal (MOL), 3) untuk mengelola Rumah Kompos yang telah ada sehingga menjadi lebih baik. Pelaksanaan pengabdian ini dititikberatkan pada beberapa kegiatan yang meliputi pengelolaan sampah organik seperti pemilahan sampah yang organik dan yang anorganik, demonstrasi pembuatan Mikro Organisme Lokal (MOL) dari bahan sisa buah-buahan dan sayuran, serta pendampingan pengelolaan rumah kompos yang baru saja dibangun di wilayah BKM Khajuma ini. Sedangkan target khusus yang ingin dicapai yaitu adanya peningkatan pengetahuan dan keterampilan masyarakat khususnya dengan adanya Rumah Kompos di tengah-tengah mereka.